2016
DOI: 10.1136/bmjopen-2015-009364
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of implementation strategies in improving physician adherence to guideline recommendations in heart failure: a systematic review protocol

Abstract: IntroductionThe uptake of Clinical Practice Guideline (CPG) recommendations that improve outcomes in heart failure (HF) remains suboptimal. We will conduct a systematic review to identify implementation strategies that improve physician adherence to class I recommendations, those with clear evidence that benefits outweigh the risks. We will use American, Canadian and European HF guidelines as our reference.Methods and analysisWe will conduct a literature search in the databases of MEDLINE, EMBASE, HEALTHSTAR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Antihypertensive therapy has demonstrated clear benefits through reducing the risk of adverse health outcomes (13). The use of treatment guidelines typically enhances the appropriate use of medicines, although there are concerns with adherence rates to guidelines in practice across countries (14)(15)(16)(17)(18). The current Kenyan Standard Treatment Guidelines (STGs) recommend the use of diuretics, beta blockers, calcium channel blockers (CCDs), angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) for patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Antihypertensive therapy has demonstrated clear benefits through reducing the risk of adverse health outcomes (13). The use of treatment guidelines typically enhances the appropriate use of medicines, although there are concerns with adherence rates to guidelines in practice across countries (14)(15)(16)(17)(18). The current Kenyan Standard Treatment Guidelines (STGs) recommend the use of diuretics, beta blockers, calcium channel blockers (CCDs), angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) for patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Las guías de práctica clínica establecen como elemento clave, el apoyo de la familia o cuidador para promover autocuidado, señalando la necesidad de valorar la capacidad y la preparación del cuidador [5][6] . Sin embargo, existen pocos estudios que evalúen la competencia de cuidado del cuidador familiar y el efecto directo sobre la experiencia de la enfermedad.…”
Section: Introductionunclassified
“…[ 6 ] Despite the existence of CPGs, the application of recommendations into routine clinical practice remains very slow. [ 7 ] However, the utility of CPGs is more important in developing its widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have examined the implementation of evidence or guidelines. [ 7 9 ] Among several methods for the implementation of CPGs, there are clinical studies that have demonstrated the applicability of CPGs to clinical fields. [ 8 , 10 13 ]…”
Section: Introductionmentioning
confidence: 99%